Research on residual stress and hydrogen diffusion of X80 pipeline welded joint - Xue, Jinghong; Cheng, Andun; Bai, Chenxu; Ji, Li (Frontiers in Materials, 2023)
Hydrogen enrichment induced by pipeline welding residual stress is a key issue affecting the safe service of hydrogen pipelines. In order to explore the influence of welding residual stress on hydrogen diffusion and the effect of heat treatment, the X80 pipeline model with a six-layer girth weld was established by using ABAQUS software, and the coupling analysis of temperature field, stress field and hydrogen diffusion was carried out. The distribution of residual stress in the welding area and local inclusion area was analyzed, the relationship between the hydrostatic stress and hydrogen diffusion of the pipeline, and the influence of the direction and shape of the inclusion on hydrogen diffusion were explored, and the effect of post-weld heat treatment on the residual stress and hydrogen diffusion in the welding area and local inclusion area was studied. The hydrostatic stress curve is similar to the hydrogen concentration distribution curve, and it can be considered that the hydrostatic stress is the main driving force for hydrogen diffusion in the pipeline. As the angle between the inclusions and the hydrogen diffusion direction increases, the hydrogen diffusion flux will gradually decrease. The more slender the inclusions, the stronger the diffusion ability of parallel or 45° inclusions, and the weaker the diffusion ability of perpendicular inclusions. Before and after post-weld heat treatment of pipeline, hydrogen enrichment occurs in inclusions or inclusion boundaries, and the internal hydrogen concentration of hard inclusions is higher than that of soft inclusions. Post-weld heat treatment can significantly reduce welding residual stress and hydrostatic stress, thereby reducing hydrogen enrichment concentration.